UNLOCKING THE DEEPER SIGNIFICANCE OF PROPHET DIALOGUES BETWEEN FATHER AND SON IN AL-QURAN: A PRAGMATIC IMPLICATURE ANALYSIS - Shabri, Irsyad; Rahma Yanti; Yalmiadi; Fhitri, Widya; Yulia, Nensi Asma (Prologue: Journal on Language and Literature, 2024)
Finding the underlying implicatures in the conversations between fathers and sons found in the Quran is the main objective of this study. It seeks to explore the hidden meanings in these exchanges and clarify the many implicatures. The Qur'an provides the qualitative and descriptive data used in this study. An observational approach is used to acquire the data, with the help of note-taking strategies and non-participant observations. The data analysis is done using the pragmatic Padan identity method along with the Determinant Element Separation Technique. To ensure a full understanding of the results, the findings are presented through an informal method. Two different types of implicatures are present, according to the results of the analysis of implicatures in the dialogic verses between father and sons of the Quran: general implicatures, and specialised implicatures. These come up in both general and focused conversations equally. Each of the dialogic verses between father and sons in the Quran contains a wide variety of interpretations, as shown by the examination of latent meanings.